(3GdMce GdbVGFj cSfO JfajPj aj bGfhf GdbVGA GdeOfj (B: s (3OQGSI ebGQfI (B/ s - (3gjcd CMeO YKeGf MejO s; (3CSGeI CMeO Thbj GdedjLj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2010)
(3jYO GdMce GdbVGFi cSfO JfajPi Cge GdhSGFd GdJi JJMbb HgG acQI GdMeGjI GdbVGFjI hJJLSO ef NdGdgG aGYdjI GdfXGe GdbVGFi hOhQg ai MeGjI GdMbhb hGdMQjGJ hGdeQGcR GdbGfhfjI hdJMbjb GdYOGdI hgh Yed bGfhfi ELQGFi Tcdi UGOQ Yf GdbVGA jJVef JCcjOG bGfhfjG (B- (3dMb HGdEdRGe (B- (3UGOQG Yf GdbVGA ZjQ efYOe heJVef EdRGeG fgGFi Ch HGJG hZjQ eJfGbVG jMed GdUhQI GdJfajPjI GdePjdI HGdUjZI GdJfajPjI (B. (3hQZe CgejI gPG GdfhY ef GdSfOGJ GdJfajPjI EdG Cf GdeTcdGJ GdJi JDOi Edi Whd GdeOi GdRefi ddMUhd Yjg Ch JYKQ JfajPg(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdYGe (B2010.s
(3HHdjhLQGajG(B: (3UaMGJ (B483-532.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdMce GdbVGFjs; (3GdbhI GdJfajPjIs; (3GdSfO GdJfajPis; (3GdfaGP GdeYLds; (3GdCSHGH h GdefWhbs; (3GdUhQI GdJfajPjIs; (3Whd GdeOj GdRefj ddJbGVjs; (3bGVj GdJfajPs; (3SbhW GdNUheIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes